2008
DOI: 10.1152/ajpgi.90214.2008
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of progesterone receptor B increases sensitivity of human colon muscle cells to progesterone

Abstract: Cheng L, Pricolo V, Biancani P, Behar J. Overexpression of progesterone receptor B increases sensitivity of human colon muscle cells to progesterone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
26
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 41 publications
5
26
0
Order By: Relevance
“…The decreased motilin level might partially be responsible for gastrointestinal hypomotility during pregnancy. These Chinese results were confirmed further by others' findings [23].…”
Section: Bowel Motility and Sex Steroid Hormonessupporting
confidence: 86%
“…The decreased motilin level might partially be responsible for gastrointestinal hypomotility during pregnancy. These Chinese results were confirmed further by others' findings [23].…”
Section: Bowel Motility and Sex Steroid Hormonessupporting
confidence: 86%
“…Indeed, several investigators have demonstrated the presence of ER and/or PR in the pelvic smooth muscle of such locations from women without endometriosis (20,21). By analogy to uterine leiomyomata, in comparison to adjacent myometrium, the increased expression of ER and/or PR in smooth muscle cells around endometriosis could be the consequence of an increased sensitivity to estrogen and/ or progesterone locally produced by endometriotic foci.…”
Section: Discussionmentioning
confidence: 99%
“…3a, b), providing novel evidence that P4 may have a direct role in controlling gastric acid secretion via mPRa signaling. The roles of mPRa in modulation of intestinal function has not been reported, even though constant expression of PR-b has been reported in the smooth muscle cells of the ileum and colon (Salomaa et al 1989) and over expression of PR-b might be associated with slow transit constipation in female patients (Cheng et al 2008). Bielefeldt et al reported that progestins exert their non-genomic effects on intestinal smooth muscle by decreasing calcium currents, which may contribute to the reduction in muscle contraction observed after P4 administration.…”
Section: Mpra In Gastrointestinal Organsmentioning
confidence: 99%